An assessment of defence policy of EU member states in 2014-2018; the cases of France, Great Britain, and Poland .......... 153 - Adamczyk, Natalia (Bezpieczeństwo regionalne: Węzłowe problemy i procesy, 2020)
As a result of the Russian annexation of Crimea and the beginning of the armed conflict in eastern Ukraine, security and defence policy was revised in many European Union countries. However, the degree of these changes varied depending on the potential represented by a given country, its security policy implemented so far and defence capabilities, including the condition and place of the army in security strategy of the state. The aim of the paper is to show the defence potentials of selected EU countries in 2014-2018, including the evolution of budget spending on defence, army composition, numbers and equipment, as well as involvement in missions and operations abroad. The most important strategic documents in the field of national security and defence will also be analysed to show political priorities and determine what modernization plans were implemented.